PERSEPSI SISWA TERHADAP PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) DAN HUBUNGANNYA DENGAN HASIL BELAJAR IPA BIOLOGI PADA SISWA KELAS VII MTS DARUL HIKMAH PEKANBARU - Agustina Supoyo; Yuslim Fauziah; Sri Wulandari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine students' perception of the implementation of cooperative learning model type Teams Games Tournament (TGT) and its relationship to learning outcomes ipa biology class VII MTs Darul Hikmah Pekanbaru. This study was conducted in May and July 2016. The sample in this study were 48 students of class and class VIIa5 VIIb4 2015/2016 school year and one science teacher. The parameters of this study (1) The students 'perception of the implementation of cooperative learning model type Teams Games Tournament (TGT) with six indicators, namely: attention, hope, motivation, needs, value systems, and personality type, (2) the relationship of students' perceptions of learning model application TGT cooperative with IPA Biology student learning outcomes. Instrument perception propagated through a closed questionnaire, the whole item questionnaire valid and reliability, koofesian reliability Cronbach Alfa of 0, 918. The data collected was analyzed mengguanakan 20:00 SPSS for windows. The results of data analysis showed that students' perceptions of 4.12 (Good). Students' perception of the implementation of cooperative learning model TGT learning outcomes Biology IPA has a close relationship (r = 0.494) in the class VII MTs Darul Hikmah Pekanbaru.